SARS-CoV-2 on Ocular Surfaces in a Cohort of Patients With COVID-19 From the Lombardy Region, Italy - Azzolini, Claudio (JAMA Ophthalmol, 2021)
IMPORTANCE: Since February 2020, coronavirus disease 2019 (COVID-19) has spread rapidly all over the world, with an epidemiological cluster in Lombardy, Italy. The viral communicability may be mediated by various body fluids, but insufficient information is available on the presence of the virus in human tears. OBJECTIVES: To investigate the rate of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in tears collected from patients with COVID-19 by means of real-time reverse transcriptase–polymerase chain reaction (rRT-PCR) assay and to assess the association of virus presence with concomitant clinical conditions. DESIGN, SETTING, AND PARTICIPANTS: Cross-sectional study conducted between April 9 and May 5, 2020. The setting was intensive care units at Azienda Socio-Sanitaria Territoriale (ASST) Sette-Laghi Hospital, University of Insubria, in Varese, Lombardy, Italy. A conjunctival swab was performed in 91 patients hospitalized for COVID-19, which was clinically diagnosed by rRT-PCR assay on nasopharyngeal swabs and by radiological imaging. Conjunctival swabs from 17 additional healthy volunteer participants with no symptoms of COVID-19 were examined to evaluate the availability and applicability of the conjunctival swab test. EXPOSURE: SARS-CoV-2 detection by means of rRT-PCR assay performed on the collected samples obtained by conjunctival swabs. MAIN OUTCOMES AND MEASURES: Conjunctival swab and nasopharyngeal swab results are reported, as well as demographic and clinical data. RESULTS: A total of 108 participants (mean [SD] age, 58.7 [14.2] years; 55 female and 53 male) were tested for SARS-CoV-2 using rRT-PCR assay, including 91 patients hospitalized with COVID-19 and 17 were healthy volunteers. SARS-CoV-2 was found on the ocular surface in 52 of 91 patients with COVID-19 (57.1%; 95% CI, 46.3%-67.5%), with a wide variability in the mean viral load from both eyes. Among a subset of 41 patients, concordance of 63.0% (95% CI, 41.0%-81.0%) was found between positive conjunctival and nasopharyngeal swab test results when performed within 2 days of each other. In 17 of these patients, nasopharyngeal swab results were negative for SARS-CoV-2. In 10 of these 17 patients, conjunctival swab results were positive for the virus. CONCLUSIONS AND RELEVANCE: In this study, SARS-CoV-2 RNA was found on the ocular surface in a large part of this cohort of patients with COVID-19, although the infectivity of this material could not be determined. Because patients may have positive test results with a conjunctival swab and negative results with a nasopharyngeal swab, use of the slightly invasive conjunctival swab may be considered as a supplementary diagnostic test.